2010
DOI: 10.1016/j.acuro.2009.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Angiomiolipoma retroperitoneal: revisión de la literatura y reporte de un nuevo caso

Abstract: Cartas científico-clínicas Angiomiolipoma retroperitoneal: revisió n de la literatura y reporte de un nuevo caso Retroperitoneal angiomyolipoma: review of the literature and report of a new case Sr. Director: Los angiomiolipomas (AML) son tumores mesenquimales benignos, compuestos por tejido adiposo maduro, mú sculo liso y vasos sanguíneos de pared engrosada, irregular y carente de fibras elá sticas. Usualmente se originan en riñ o ´ n, y muy raras veces en o ´ rganos extrarenales como hígado, regiones ginecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
2
0
7
Order By: Relevance
“…The vast majority of AMLs primarily involve one or both kidneys. However, extrarenal AMLs have also been reported in several tissues, including the mediastinum, the retroperitoneum, the abdominal wall, the heart, the lungs, the stomach, the spleen, the bones, the transverse colon, the vagina, the upper lip, the nasal cavity, the spinal cord, the parotid glands and the skin ( 5 , 9 – 13 ). Duodenal AMLs are markedly rare and present clinically with satiety, melena, anemia, generalized weakness, vomiting and abdominal pain ( 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of AMLs primarily involve one or both kidneys. However, extrarenal AMLs have also been reported in several tissues, including the mediastinum, the retroperitoneum, the abdominal wall, the heart, the lungs, the stomach, the spleen, the bones, the transverse colon, the vagina, the upper lip, the nasal cavity, the spinal cord, the parotid glands and the skin ( 5 , 9 – 13 ). Duodenal AMLs are markedly rare and present clinically with satiety, melena, anemia, generalized weakness, vomiting and abdominal pain ( 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Daniel et al [ 27 ] reported a 34-year-old woman who underwent excision of a large left retroperitoneal mass which had extended between the diaphragm and the bifurcation of the iliac vessels. They stated that the pathological features of the lesion were consistent with the diagnosis of retroperitoneal angiomyolipoma (RAML) and their reported case was the 19th case of extrarenal retroperitoneal angiomyolipoma (ERAML) to be reported.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hay reportes de casos que describen que se asocian a mortalidad materna (7,8). Son condiciones especiales en el embarazo, el hemangioma retroperitoneal, que puede presentar expansión significativa, probablemente por los factores vasoactivos secretados durante la gestación, lo que resulta en vasodilatación periférica (9), y el angiolipoma, que experimenta un crecimiento significativo, lo que indica una dependencia hormonal por la presencia de receptores de estrógenos y progesterona en las células musculares lisas (10).…”
Section: Introductionunclassified